POTENTIAL OF INDIGENOUS PROBIOTIC Lactobacillus plantarum Dad 13 AS ANTIâDIARRHEA AND IMMUNOâMODULATOR - Sudarmi, Agustina Intan Niken Tari, Catur Budi Handayani & (Proceeding of International Congress, 2014)
The purpose of the research were to study the effectivity of selected indigenous probiotic Lactobacillusplantarum Dad 13 against enteropathogenic E. coli causing diarrhea in vivo as well as sinbiotic immunomodulatoryproperties of purple sweet potato extract probiotic yogurt on blood and liver MDA levels inalbino Norway rats (Rattus novergicus) Sprague dawley strain. Unidirection factorial completely randomizeddesign was applied during study with several variables: purple sweet potato yogurt without probioticsaddition (P0) and with probiotic addition (P1), where the latter was conducted on two groups of SpragueDawley rats treated with or without EPEC ATCC 35218 enteropathogenic Escherichia coli (E1 or E0, respectively).Results showed that there was interaction between indigenous probiotic addition in purple sweetpotato yogurt and EPEC ATCC 35218 on faecal water content after 1 week treatment with EPEC ATCC35218, cecum water content, and MDA level of blood and liver of experimental animals at the end of thestudy. Besides, culture of Lactobacillus plantarum Dad 13 added to purple sweet potato extract yogurt wasable to provide preventive health effects as antiâdiarrhea and immunomodulatory agent.Keywords: Probiotic, Antiâdiarrhea, Immunoâmodulator